2021
DOI: 10.3390/healthcare9040457
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Recreational Small-Sided Soccer Games on Bone Mineral Density in Untrained Adults: A Systematic Review and Meta-Analysis

Abstract: This systematic review with meta-analysis was conducted to assess the effects of small-sided games (SSG)-based training programs on bone mineral density (BMD) in untrained adults. The data sources utilized were Cochrane, Embase, Medline (PubMed), Scopus, SPORTDiscus, and Web of Science. The study eligibility criteria were: (i) untrained adults (>18 years old) of any sex, with or without a noncommunicable disease; (ii) SSG-based programs with a minimum duration of four weeks and no restrictions regarding fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…The findings of the present study are supportive of two recent meta-analyses (Ashe et al, 2021 ; Clemente et al, 2021 ). Ashe and colleagues (Ashe et al, 2021 ) suggested that physical activity has little effect on the total hip BMD, and little to no effect on femoral neck BMD, lumbar spine BMD, and WB BMD in males.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of the present study are supportive of two recent meta-analyses (Ashe et al, 2021 ; Clemente et al, 2021 ). Ashe and colleagues (Ashe et al, 2021 ) suggested that physical activity has little effect on the total hip BMD, and little to no effect on femoral neck BMD, lumbar spine BMD, and WB BMD in males.…”
Section: Discussionsupporting
confidence: 92%
“…Ashe and colleagues (Ashe et al, 2021 ) suggested that physical activity has little effect on the total hip BMD, and little to no effect on femoral neck BMD, lumbar spine BMD, and WB BMD in males. The other meta-analysis assessed the effects of small-sided games-based training programs on BMD in untrained adults (Clemente et al, 2021 ) and reported a trivial effect and small effect for this type of training on the WB BMD and lower limbs BMD, respectively when compared to the control groups. The modest osteogenic expression found in the WB BMD, compared to other bone sites, could reflect a site-specific effect for physical exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The diversity of systematic reviews in recreational soccer is clear from the extant literature [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. As can be seen from the available systematic reviews, some have focused on specific outcomes, such as bone health [ 26 , 27 ], fat mass [ 22 ], or maximal oxygen uptake [ 20 ], while others summarized the effects on different outcomes [ 21 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of systematic reviews in recreational soccer is clear from the extant literature [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. As can be seen from the available systematic reviews, some have focused on specific outcomes, such as bone health [ 26 , 27 ], fat mass [ 22 ], or maximal oxygen uptake [ 20 ], while others summarized the effects on different outcomes [ 21 , 23 , 24 , 25 ]. Additionally, half of these systematic reviews were exclusively dedicated to adult populations [ 21 , 22 , 26 , 27 ], while the remaining reviews focused on mixed populations, such as children, adolescents, adults, and older individuals (both healthy and unhealthy), thus making it difficult to determine a clear overview of the effects on children and youths [ 20 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Small-sided games (SSGs) are a form of conditioning in football [ 1 , 2 , 3 ] and represent an effective alternative to traditional interval training in order to improve players’ endurance with a concomitant physical, cognitive and technical/tactical development [ 1 , 2 , 4 , 5 , 6 , 7 ]. SSGs are now very popular because they are suitable not only for elite football players, but also for healthy and unhealthy amateurs; they enhance several components of the health-related fitness: in fact, recreational football, carried out as SSGs, has a high aerobic component (80–85% maximum heart rate, HRmax), provides a high impact on muscles and bones, and improves maximum aerobic power blood pressure and body composition [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%